Film, kritika, kontekst: 'Sami' - Brlek, Tomislav (Array, 2002)
The article offers an analysis of the critical readings of the film 'Alone' (2001) by Lukas Nola, focusing on the theoretical tenets underpinning those interpretations, regardless of their respective evaluative assessments of the film. The theoretical articulation of the referential frame operative in the reviews analysed is found in the works of Hrvoje Turković, especially in his 'Theory of Film' (1994). Given that any interpretation is determined by its chosen theoretical perspective, the analysis endeavours to expose the inadequacies and exclusions peculiar to this interpretative procedure and to demonstrate that the reading of the film 'Alone' would yield significantly different results if studied within the semiotic perspective.